Impact of hyperhydration on fluid overload and hematopoietic cell transplant after post-transplant cyclophosphamide-based graft-versus-host-disease prophylaxis - Samuels, Diana T.; Yao, Janny M.; Samara, Yazeed; Yang, Dongyun; Mokhtari, Sally; Tiemann, Katrin; Otoukesh, Salman; Arslan, Shukaib; Pourhassan, Hoda; Wu, Stephanie; Blackmon, Amanda; Agrawal, Vaibhav; et al. (Frontiers in Immunology, 2025)
IntroductionHemorrhagic cystitis (HC) is an early complication after hematopoietic cell transplant (HCT) with post-transplant cyclophosphamide (PTCy). Hyperhydration can reduce HC, but may lead to fluid overload (FO), which has been associated with higher non-relapse mortality (NRM) after HCT.MethodsThe objectives of this study were to grade FO between days 3 and 8 based on weight gain, diuretic therapy, and FO-related organ dysfunction and analyze the impact of FO on non-relapse mortality (NRM) and subsequently on overall survival (OS) of patients undergoing HCT with PTCy-based GvHD prophylaxis.ResultsTwo hundred seventy-five patients who received PTCy at City of Hope from 2009 to 2018 were included. A majority, 270 (98%) patients were diagnosed with early FO from day 3-8 post HCT, of whom 248 (92%) experienced mild to moderate (grade 1-2) FO, and 22 (8%) experienced severe (grade 3-4) FO. Day 100 NRM was significantly higher in patients with grade 3-4 FO compared to patients with grade 0-1 (59.1 vs 1.7%, CI: 0.006-0.053p<0.001) and grade 2 (59.1 vs 8.8%, CI: 0.043-0.178, p<0.001) FO. At 2 years, OS and DFS were significantly lower in patients who experienced grade 3-4 FO compared to patients who had grade 0-1 FO (31.8% vs 68.2%, CI: 0.616-0.755, p<0.001) and grade 2 FO (31.8% vs 62.5%; CI: 0.527-0.741, p<0.001). Additionally, each 5% weight gain from baseline was associated with higher NRM (HR=1.91, 95%CI: 1.64-2.23, p<0.001).ConclusionAlmost all patients undergoing hyperhydration for PTCy-induced HC will present with FO. Grade 3-4 FO is uncommon and associated with poor clinical outcomes. Weight gain could be used as an early and possibly modifiable indicator of FO.